Integrated Management of Phosphorus, Organic Sources, and Beneficial Microbes Improve Dry Matter Partitioning of Maize. Issue 20 (13th November 2019) - Amanullah,; Iqbal, Asif; Khan, Adil; Khalid, Shah; Shah, Azizullah; Parmar, Brajendra; Khalid, Shah; Muhammad, Asim
ABSTRACT: Phosphorus (P) unavailability and lack of organic matter in the soils under semiarid climates are the two major constraints that negatively influence dry matter partitioning and yield in maize. Three field experiments were conducted to investigate the impact of phosphorus, organic sources and phosphate solubilizing bacteria (PSB) on dry matter partitioning (DMP) of maize during summer 2014 and 2015. The experiments were carried out at Agronomy Research Farm, The University of Agriculture Peshawar. The results revealed that application of P at the rate of 75–100 kg P ha −1 for open pollinated variety and 120 kg P ha −1 for hybrid maize was more beneficial in terms of higher DMP and accumulation. Application of compost at sowing time along with poultry manure (5 tons ha −1 ), 2 weeks before sowing of maize increased DMP significantly. The results further suggested that incorporation of legume (faba bean) residues (10 tons ha −1 ) 1 month before sowing significantly increased DMP in maize as compared to the incorporation of garlic and paper mulberry residues. The results confirmed that seed inoculation with PSB increases the availability of calcium bound-phosphorus under calcareous soils in semiarid climates hence increased DMP and accumulation, and total maize biomass.